Sistem Pendukung Keputusan Kelompok Promosi Jabatan dengan Metode AHP dan BORDA - Sugiartawan, Putu; Prakoso, Paholo Iman (INFOTEKS (Information Technology, Computer and Sciences), 2019)
Abstract Determination of the best employees in a company aims to improve competitiveness and give awards to employees who have high dedication to the company. Difficulties in evaluating employees are the many assessment factors and characteristics of the appraisal and who will provide the appraisal, so that the appraisal is appropriate and transparent. Employee performance appraisal is carried out by 2 assessors namely the company manager and the head of the human resource management department (HRD) and consists of a number of criteria. The assessment will be difficult if done manually considering that each assessor has their own preferences in conducting the assessment. To overcome this we need a computer system that helps decision making, namely a group decision support system (GDSS) determining the best employees in a company The group decision support system developed in this study uses the AHP and BORDA methods to assist group decision making. AHP method is used for decision making in each appraiser, while the Borda method is used to combine the decision results of each appraiser so that the final result is the best employee in the company. Based on the final results of the best employee determination system in the form of ranking the final value of each employee. The highest value is used as a recommendation as the best employee.